Development of a robotic boiler header inspection device with redundant localization system - Basri N.M.H.; Sahari K.S.M.; Anuar A. (Fuji Technology Press, 2023)
A pipe inspection robot, called a boiler header inspection robot (BHIR), is presented in this paper. The BHIR was designed specifically to inspect the inner surfaces of horizontal boiler header pipes in a thermal power plant in Malaysia that is owned by Tenaga Nasional Berhad (TNB). The main challenge was the geometry of a boiler header pipe: the entry diameter is significantly smaller than the diameter of the main pipe body. Currently, there are two versions of the BHIR: 1) the first version, BHIR-I, which was developed for use in manual inspections by carrying a borescope camera inside a boiler header pipe, and 2) the second version, BHIR-II, which has an onboard visual inspection system that can inspect pipes and acquire images independently. The robot was designed to be able to navigate through the pipe geometry. A unique redundant localization system that uses an accelerometer and encoder sensor was developed to ensure that the robot knows the location of the images taken and its own position inside the boiler header pipe. This paper discusses the prototype development, the localization system and site testing conducted to validate the prototype. Based on the test results, the BHIR prototype with redundant localization was proven to be successful.